2018
DOI: 10.1094/mpmi-12-17-0313-r
|View full text |Cite
|
Sign up to set email alerts
|

The Coiled-Coil and Leucine-Rich Repeat Domain of the Potyvirus Resistance Protein Pvr4 Has a Distinct Role in Signaling and Pathogen Recognition

Abstract: The pepper Pvr4 protein encoding coiled-coil (CC) nucleotide-binding (NB) leucine-rich repeat (LRR) (NLR) confer hypersensitive response (HR) to potyviruses, including Pepper mottle virus (PepMoV), by recognizing the viral avirulence protein NIb. To figure out the Pvr4-mediated HR mechanism, we analyzed signaling component genes and structure-function relationships of Pvr4, using chimeras and deletion mutants in Nicotiana benthamiana. Molecular chaperone components including HSP90, SGT1, and RAR1 were required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…Silencing or mutation of any one of RAR1, SGT1 or HSP90 in many interactions is sufficient to abolish HR and to cause the reduction of NLR protein levels (e.g. Azevedo et al , ; Bieri et al , ; Hubert et al , ; Kim et al , ; Scofield et al , ). The role of SGT1 is not completely understood.…”
Section: Controlmentioning
confidence: 99%
“…Silencing or mutation of any one of RAR1, SGT1 or HSP90 in many interactions is sufficient to abolish HR and to cause the reduction of NLR protein levels (e.g. Azevedo et al , ; Bieri et al , ; Hubert et al , ; Kim et al , ; Scofield et al , ). The role of SGT1 is not completely understood.…”
Section: Controlmentioning
confidence: 99%
“…This clearly shows that Ry sto 's mode of action is EDS1-and NRG1-dependent ( Fig. 5), while Pvr-4 mediated ER to PVY infection in N. benthamiana is EDS1-independent (Kim et al 2018).…”
Section: Discussionmentioning
confidence: 85%
“…These genes are genetically linked 34 and oriented head-to-head so that they may share a promoter for simultaneous regulation of 35 transcription. Although in silico analyses revealed that NLRs with integrated domains are 36 common in higher plants, functional NLR pairs have been discovered in only a few plant 37 species (15). A more complex NLR model was reported as an 'NLR network', primarily in 38 Solanaceous plants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sequences of these 109 upstream NLR genes did not encode an integrated decoy domain, which is a typical feature of Although ROS production and upregulation of defense-related genes are typical immune 168 responses, we cannot exclude the possibility that they also occur as a consequence of cell 169 death. To verify that autoactive G10-NLR and G10-CC indeed trigger defense responses, we 170 performed a co-expression assay using a Potato virus X (PVX) vector encoding GFP (37). 171 We hypothesized that if autoactive G10-CC-or G10-NLR-mediated cell death is associated Recent studies revealed that NLR-mediated immunity involves a complex network and 267 many NLRs require helper NLRs to exert activity in the immune response (16,22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation